非定形口蓋裂に対し口蓋形成術を施行した両側性斜顔面裂の1例 - 横田, 祐介; 美馬, 孝至; 山西, 整; 飯田, 征二; 古郷, 幹彦; 相川, 友直 (日本口腔外科学会雑誌, 2011)
Oblique facial cleft is a very rare congenital anomaly. Little has been published about the surgical treatment of facial and palatal clefts in such cases. We encountered a patient with Tessier No. 4 and No. 5 oblique facial clefts accompanied by an atypical bilateral palatal cleft in Mexico during a charity medical campaign. This campaign is supported by Japan International Cooperation Agency (JICA), the mission of which is to bring surgical treatments to Mexican patients with clefts who have difficulties in receiving medical treatments because of economic reasons. We repaired the facial clefts when the patient was 14 months old, and previously reported a summary of the treatment. We now describe the details of palatoplasty applied to the atypical bilateral cleft palate of the patient. Because the palatal clefts were so wide and asymmetric’conventional push-back palatoplasty was not applicable. We used a modification of double opposite Z plasty, proposed by Furlow in 1972, for palate surgery. The patient’s age was 2 years 3 months. Since the patient had microphthalmia in the right eye, we also placed an ocular prosthesis in the right orbital cavity to retain the bone structure of the midface.